Parental acceptance of school-based universal depression screening for children and adolescents in primary and secondary school in China - Peipei Wu; Wenjuan Huang; Feng Jiao; Guoping Chen; Ying Sun (BMC Public Health)
Abstract Introduction School-based universal depression screening (SBUDS) is an effective method for early identification of depression. As parents are the primary decision-makers for their children’s acceptance of healthcare services, this study aims to examine rural and urban parental acceptance of SBUDS. Methods The study assessed parental acceptance of SBUDS for their children and its association with self-reported parental perception of depression (i.e., parental knowledge of depression, self-efficacy to identify child depression, and depression stigma) and parental belief regarding the benefits and risks of SBUDS. The analysis included 13,480 parents with at least one child in grades 4–12 from 29 primary and secondary schools in four cities across China. Results In this large and diverse sample, 92.4% of the participants supported SBUDS for their children despite concerns about the risks of SBUDS (e.g., accuracy and privacy of screening results). Most parents supported SBUDS starting in 4th (25.5%) or 7th (24.7%) grades, though 7.6% responded no screening should be done. Regression analysis revealed that parents with a higher level of knowledge about depression (OR = 1.496, 95%CI [1.08, 2.073]; P = 0.015) had higher odds of parental acceptance of SBUDS. However, this association was not evident among rural parents stratified by urban-rural locality. Conclusions In this survey study, most Chinese parents accept SBUDS for their children despite concerns. Guidelines for maintaining adolescent confidentiality and ensuring the accuracy of results in an SBUDS will require careful consideration. Additionally, the study findings indicate that improving parental knowledge about adolescent depression is essential for promoting parental acceptance of SBUDS.